Desentralisasi dalam Perspektif Technology Trend terhadap Blockchain dan Web3 (Journal Digital Technology Trend, 2023)
This study explores the concept of decentralization in the context of emerging technologies, specifically Blockchain and Web3. These technologies offer an alternative to traditional centralized models by promoting systems that are more open, secure, and transparent. The study employs a qualitative approach using case studies to understand the practical applications and impacts of decentralization across various industries. Key findings highlight the significant benefits of decentralization, such as enhanced security and transparency, user control over data, and operational efficiency through smart contracts. However, challenges such as scalability, regulatory compliance, and security concerns remain. The study concludes that while there are considerable challenges, the benefits of decentralization make it a promising area for continued exploration and development. With sustained research and technological advancement, broader adoption and deeper integration into everyday life can be achieved, leading to a more decentralized and inclusive digital future.